Microgrid Design in Electricity Supply in Paper Factories - Arief Pratomo Sitompul; Dhami Johar Damiri (International Journal of Social Service and Research, 2023)
Renewable energy is growing, one of which is by controlling solar energy. A solar power plant (PLTS) is a power generation system that utilizes solar energy to become electrical energy through photovoltaic modules, which are included in environmentally friendly energy so that it becomes a renewable, effective, more efficient, and reliable plant. The research designing the modeling of PLTS on a grid was carried out on the roof of a gas power plant (PLTG) which generated 164.47 MWh / year. Analyzing modeling in the addition of the Rooftop Solar System that enters the network can reduce exhaust emissions from the use of other equipment for four years with an average of PLN by 99.29%, PLTG #1 by 99.06 and PLTG #2 by 99.11%. The impact of the addition of the PLTS Rooftop on the quality of power entering the 3.3 kV network system is seen that the feeder 2-panel bus has improved to 97.82% of the voltage drop of 72.67% in line with the PLN 3 panel, the improvement is made by providing capacitors of 3x4Mvar. Feeder 3 improved to 97.61% of the voltage drop of 78.87%, in line with the PLN 4 panel. The improvement was carried out by providing a capacitor of 2x4Mvar. Panel feeder four was seen to have improved to 99.21% from an excess voltage of 109.23% in line with the generating equipment, and the improvement was made by reducing capacitors by 0.1 Mvar from the used 5x0.1 Mvar.